Assistance in identifying and cultivating medicinal plant to prepare herbal tourism in Cisantana Village, Kuningan District - Anwarudin, Wawang; Azizah, Nur; Darotulmutmainnah, Azmi; Wardaya, Ahmad Wildhan Wisnu; Puspita, Diah Ayu; Alfarra, Fathya Rayhan (Community Empowerment, 2025)
Cisantana Village is endowed with abundant natural resources due to its geographical location on the slopes of Mount Ciremai, making it a potential tourist village. However, this potential has not been optimally utilized due to the lack of proper management of the village's land resources. Therefore, providing assistance in identifying and cultivating medicinal plants has emerged as a viable solution to prepare Cisantana as a Herbal Tourism destination. This community service activity aimed to disseminate information about medicinal plants identified through exploration and expeditions in Cisantana Village, and to enhance participants' skills in cultivating these valuable plants. The participants in this activity were members of the Dahlia Integrated Health Post Working Group and the Cisantana Village Government. The results of the activity revealed that there are 26 types of herbal plants in Cisantana Village. Furthermore, there was an increase in public understanding of the benefits of medicinal plants, from 65% to 80%, and an increase in understanding of how to cultivate medicinal plants, from 70% to 85%.